Preparation method of antistatic modified chinlon filament

By introducing modified multi-walled carbon nanotubes and specific chemical groups into the nylon filaments, anti-static modified nylon filaments are prepared, which solves the problems of degradation in performance and electrostatic fire of nylon materials under high temperature or light conditions, and achieves better anti-static, flame retardant, mechanical and anti-aging properties.

CN119553384AInactive Publication Date: 2025-03-04GUANGDONG JINSHI NEW MATERIALS TECHNOLOGY CO LTD
View PDF 0 Cites 4 Cited by

Patent Information

Application Number
CN202510101018.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-22
Publication Date
2025-03-04
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

Nylon materials are prone to soften and turn yellow in high temperature environments or strong light conditions, and are prone to accumulation of static electricity and causing fire accidents.

Method used

The benzooxazole diethyl pyrrole phosphate was prepared by reacting diethyl (formylmethyl)phosphate and 1-aminopyrrole, and then reacting with hydroxylated multi-walled carbon nanotubes to obtain modified multi-walled carbon nanotubes. The benzooxazole diamide monomer was prepared by reacting with 2,2'-bipyridine-5,5'-dicarboxylic acid and 2-amino-5-nitrophenol. Finally, the anti-electrostatically modified nylon filaments were mixed with modified polyamide, modified multi-walled carbon nanotubes, pyrrole, ferric chloride and copper chloride and melt-spinned to make anti-static modified nylon filaments.

Benefits of technology

The anti-static, flame retardant properties, mechanical properties and anti-aging properties of anti-static modified nylon filaments are improved, and the deformation and electrostatic fire risks under high temperature or strong light conditions are reduced.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_10
    Figure SMS_10
  • Figure QLYQS_1
    Figure QLYQS_1
  • Figure QLYQS_2
    Figure QLYQS_2
Patent Text Reader

Abstract

The invention discloses a preparation method of antistatic modified chinlon filaments, and relates to the field of chinlon filaments. When the antistatic modified chinlon filament is prepared, (formylmethyl) diethyl phosphate and 1-aminopyrrole react to prepare pyrrole diethyl phosphate; reacting the hydroxylated multi-walled carbon nanotube with pyrrole diethyl phosphate to obtain a modified multi-walled carbon nanotube; the preparation method comprises the following steps: reacting 2, 2 '-bipyridine-5, 5'-dicarboxylic acid with 2-amino-5-nitrophenol, and then reducing to obtain a benzoxazole diamine monomer; then, adipic acid, 1, 5-diaminopentane and a benzoxazole diamine monomer are subjected to a reaction, and modified polyamide is prepared; uniformly mixing the modified polyamide, the modified multi-walled carbon nanotubes, pyrrole, ferric trichloride and copper chloride, and performing melt spinning to obtain the antistatic modified polyamide filament. The antistatic modified chinlon filament prepared by the invention has excellent antistatic, flame-retardant, anti-aging and mechanical properties.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of nylon filaments, and in particular to a method for preparing antistatic modified nylon filaments. Background Art

[0002] Polyamide was first produced in Jinzhou, so its Chinese name is also called nylon. Nylon is its English product name, so polyamide is also called nylon. Nylon is the oldest synthetic fiber in the world and has been industrialized for the longest time. There are many different varieties of nylon, which can be divided into aliphatic and aromatic according to their chemical structure. Among synthetic fibers, nylon has the best wear resistance, high breaking strength, high breaking elongation, excellent acid resistance, and good hydrophilicity, which is only slightly lower than polyester among many synthetic fibers. In addition to the common characteristics of synthetic fibers such as corrosion resistance, mildew resistance, and low regain, nylon filament also has the advantages of high strength and excellent wear resistance. Nylon has a high acceptance of acid dyes and has good overall dyeability. Therefore, in the field of clothing textiles, high-end underwear, sports backpacks, sportswear and other product directions have a stable market share.

[0003] Although nylon has many advantages, it still has many disadvantages. For example, in a high temperature environment or an environment with strong light, nylon will soften, turn yellow, and lose strength over time, that is, nylon has poor light resistance and heat resistance; nylon has a low initial modulus, which will cause nylon products to be relatively easy to deform during use. In recent years, with the widespread use of nylon materials, fires and explosions caused by static electricity generated by nylon materials have increased year by year. This is because nylon materials basically link each element in the form of covalent bonds, which prevents ionization and charge transfer. Therefore, nylon materials have high insulation properties, are prone to static electricity accumulation, generate sparks, ignite themselves or surrounding combustibles to form a fire source, and then cause a fire. Therefore, the present invention prepares an antistatic modified nylon filament with excellent flame retardant properties. Summary of the invention

[0004] The purpose of the present invention is to provide a method for preparing antistatic modified nylon filaments to solve the problems existing in the prior art.

[0005] In order to solve the above technical problems, the present invention provides the following technical solutions: a method for preparing antistatic modified nylon filaments, wherein the antistatic modified nylon filaments are prepared by melt spinning after mixing modified polyamide, modified multi-walled carbon nanotubes, pyrrole, ferric chloride and cupric chloride.

[0006] As an optimization, the modified polyamide is prepared by reacting 2,2'-bipyridine-5,5'-dicarboxylic acid with 2-amino-5-nitrophenol, and then reacting with adipic acid and 1,5-diaminopentane.

[0007] As an optimization, the modified multi-walled carbon nanotubes are prepared by reacting diethyl (formylmethyl) phosphate with 1-aminopyrrole and then reacting with hydroxylated multi-walled carbon nanotubes.

[0008] As an optimization, the hydroxylated multi-walled carbon nanotubes are from Suzhou Beike Nanotechnology Co., Ltd.

[0009] A method for preparing antistatic modified nylon filaments comprises the following preparation steps: (1) Mix diethyl (formylmethyl) phosphate, 1-aminopyrrole, anhydrous magnesium sulfate, glacial acetic acid and anhydrous ethanol in a mass ratio of 1: (0.4-0.6): (0.6-0.8): (0.3-0.4): (17-19), reflux at 65-75°C in a nitrogen atmosphere for 5-7 hours, cool naturally to room temperature and filter, wash with deionized water and anhydrous methanol for 3-5 times respectively, and dry at 75-85°C for 11-13 hours to obtain diethyl pyrrole phosphate. ; Mix hydroxylated multi-walled carbon nanotubes, diethyl pyrrole phosphate, tetrabutyl titanate and toluene in a mass ratio of 1: (1-3): (0.01-0.02): (5-7), stir at 155-165°C and 200-300rpm for 4-6 hours in a nitrogen atmosphere, cool naturally to room temperature and filter, wash with deionized water and anhydrous ethanol for 3-5 times respectively, dry at 60-70°C for 23-25 ​​hours, grind and sieve 55-65 mesh to obtain modified multi-walled carbon nanotubes; (2) Mix 2,2'-bipyridine-5,5'-dicarboxylic acid, 2-amino-5-nitrophenol and polyphosphoric acid in a mass ratio of 1:(1.2-1.4):(18-19), stir at 55-65°C and 100-200 rpm for 5-7 h in a nitrogen atmosphere, cool to 35-45°C, pour into deionized water, stir at 900-1100 rpm until the precipitate mass remains unchanged, filter, and dilute with 0.4-0.6 mol / L sodium hydroxide solution and deionized water, respectively. Wash 3 to 5 times, dry at 100 to 110°C for 6 to 8 hours to obtain a benzoxazole intermediate; mix the benzoxazole intermediate, palladium carbon and N-methylpyrrolidone in a mass ratio of 1: (0.06 to 0.08): (9 to 11), stir in a hydrogen atmosphere at 20 to 30°C and 100 to 200 rpm for 23 to 25 hours, filter, pour into deionized water, stir until the precipitate remains unchanged in mass, filter, and dry at 55 to 65°C for 8 to 10 hours to obtain a benzoxazole diamine monomer; (3) 1,5-diaminopentane adipate, benzoxazole diamino adipate and deionized water are mixed in a mass ratio of 1: (0.7-0.9): (15-25), stirred for 55-65 min at 215-225° C., 1-3 MPa and 300-400 rpm in a nitrogen atmosphere, heated to 265-276° C. for vacuum polymerization for 0.5-1.5 h, allowed to stand for 10-20 min, discharged from the supercooled water and sliced ​​to obtain a modified polyamide; (4) The modified polyamide, modified multi-walled carbon nanotubes, pyrrole, ferric chloride and cupric chloride are mixed in a mass ratio of 1: (0.04-0.06): (0.02-0.03): (0.01-0.02): (0.01-0.03), and the mixture is extruded and spun using a twin-screw extruder. The mixture is allowed to stand at 95-105°C for 6-8 hours and naturally cooled to room temperature to obtain antistatic modified nylon filament.

[0010] As an optimization, the reaction equation of diethyl pyrrole phosphate in step (1) is: .

[0011] As an optimization, the reaction equation for modifying the multi-walled carbon nanotubes in step (1) is: .

[0012] As an optimization, the reaction equation of the benzoxazole diamine monomer in step (2) is: .

[0013] As an optimization, the 1,5-diaminopentane adipate in step (3) is prepared by mixing adipic acid and anhydrous ethanol in a mass ratio of 1:(14-16), stirring at 55-65°C and 100-200 rpm for 25-35 min, adding 1,5-diaminopentane in an amount of 0.6-0.8 times the mass of adipic acid at a uniform rate within 55-65 min, heating to 70-80°C and reflux for 2-4 h, naturally cooling to room temperature and filtering, washing with anhydrous ethanol for 3-5 times, and drying at 65-75°C for 11-13 h.

[0014] As an optimization, the benzoxazole diamino adipate in step (3) is prepared by mixing adipic acid and anhydrous ethanol in a mass ratio of 1:(14-16), stirring at 55-65°C and 100-200 rpm for 25-35 min, adding benzoxazole diamino monomer 2-3 times the mass of adipic acid at a uniform rate within 55-65 min, heating to 70-80°C and reflux for 2-4 h, naturally cooling to room temperature and filtering, washing with anhydrous ethanol for 3-5 times, and drying at 65-75°C for 11-13 h.

[0015] As an optimization, the reaction equation of the modified polyamide in step (3) is: ; R1 is ; R2 is .

[0016] As an optimization, the reaction equation of the antistatic modified nylon filament in step (4) is: ; Where R1 is R2 is .

[0017] As an optimization, the main process parameters of the spinning process in step (4) are: zone 1 245°C, zone 2 250°C, zone 3 250°C, zone 4 255°C, zone 5 255°C, side blowing temperature of 16.5°C, wind speed of 0.4 m / s, stretching temperature of 140-150°C, and stretching multiple of 1.2.

[0018] Compared with the prior art, the beneficial effects achieved by the present invention are as follows: when preparing the antistatic modified nylon filament, (formylmethyl) diethyl phosphate and 1-aminopyrrole are reacted to obtain pyrrole diethyl phosphate; then hydroxylated multi-walled carbon nanotubes and pyrrole diethyl phosphate are reacted to obtain modified multi-walled carbon nanotubes; 2,2'-bipyridine-5,5'-dicarboxylic acid and 2-amino-5-nitrophenol are reacted and then reduced to obtain benzoxazole diamine monomer; then adipic acid, 1,5-diaminopentane and benzoxazole diamine monomer are reacted to obtain modified polyamide; and the modified polyamide, modified multi-walled carbon nanotubes, pyrrole, ferric chloride and cupric chloride are mixed and then melt-spun to obtain the antistatic modified nylon filament.

[0019] Firstly, diethyl (formylmethyl) phosphate and 1-aminopyrrole are reacted to obtain diethyl pyrrole phosphate; then, hydroxylated multi-walled carbon nanotubes and diethyl pyrrole phosphate are reacted to obtain modified multi-walled carbon nanotubes; diethyl pyrrole phosphate is obtained by Schiff base reaction, so that pyrrole rings and phosphorus elements can be directly grafted on multi-walled carbon nanotubes through ester exchange reaction, and multi-walled carbon nanotubes are used as fillers to improve the antistatic property of antistatic modified nylon filaments; pyrrole on the surface of modified multi-walled carbon nanotubes can form long polypyrrole chains, and polypyrrole The polypyrrole molecule contains a conjugated structure that can provide free electrons, providing a charge conduction channel, further improving the antistatic properties of the antistatic modified nylon filament; at the same time, the nitrogen atoms in polypyrrole can coordinate with metal ions to form metal-nitrogen coordination bonds and a cross-linked network, thereby improving the mechanical properties of the antistatic modified nylon filament; the grafting of phosphorus elements enables the formation of a protective layer during the combustion process, and can also capture free radicals in the combustion flame, cut off the flame oxidation chain reaction, and improve the flame retardant properties of the antistatic modified nylon filament.

[0020] Secondly, 2,2'-bipyridine-5,5'-dicarboxylic acid and 2-amino-5-nitrophenol are reacted and then reduced to obtain benzoxazole diamine monomer; adipic acid, 1,5-diaminopentane and benzoxazole diamine monomer are then reacted to obtain modified polyamide; modified polyamide, modified multi-walled carbon nanotubes, pyrrole, ferric chloride and cupric chloride are mixed and melt-spun to obtain antistatic modified nylon filaments; benzoxazole intermediates are generated by cyclodehydrogenation under the action of polyphosphoric acid, and benzoxazole diamine monomers are obtained by reducing the nitro group. The molecular structure of the benzoxazole diamine monomer has a large number of conjugated π-π* transition π electron systems. It has a strong absorption capacity for the invisible ultraviolet light (300-400nm) in sunlight, and can convert it into visible light wavelength of 420-440nm and reflect it, thereby improving the anti-aging performance of the antistatic modified nylon filament; at the same time, the bipyridine structure contained in the benzoxazole diamine monomer can coordinate with metal ions to form a stable metal-ligand cross-linked network between the polyamide main chain and the modified multi-walled carbon nanotubes. The electron cloud distribution of bipyridine itself can also affect the electron density of the metal center, promote the migration of electrons, and improve the mechanical properties and antistatic properties of the antistatic modified nylon filament. DETAILED DESCRIPTION

[0021] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0022] The hydroxylated multi-walled carbon nanotubes described in the following examples and comparative examples are from Suzhou Beike Nanotechnology Co., Ltd.; the main process parameters of the spinning process described in the following examples and comparative examples are: 245°C in zone one, 250°C in zone two, 250°C in zone three, 255°C in zone four, 255°C in zone five, side blowing temperature of 16.5°C, wind speed of 0.4m / s, stretching temperature of 145°C, and stretching multiple of 1.2.

[0023] Example 1 A method for preparing antistatic modified nylon filaments, the method comprising the following preparation steps: (1) Diethyl (formylmethyl) phosphate, 1-aminopyrrole, anhydrous magnesium sulfate, glacial acetic acid and anhydrous ethanol were mixed in a mass ratio of 1:0.4:0.6:0.3:17, refluxed at 65°C for 7 h in a nitrogen atmosphere, naturally cooled to room temperature and filtered, washed with deionized water and anhydrous methanol three times respectively, and dried at 75°C for 13 h to obtain diethyl pyrrole phosphate; hydroxylated multi-walled carbon nanotubes, diethyl pyrrole phosphate, tetrabutyl titanate and toluene were mixed in a mass ratio of 1:1:0.01:5, stirred at 155°C and 200 rpm for 6 h in a nitrogen atmosphere, naturally cooled to room temperature and filtered, washed with deionized water and anhydrous ethanol three times respectively, dried at 60°C for 25 h, and ground and sieved through 55 mesh to obtain modified multi-walled carbon nanotubes; (2) 2,2'-bipyridine-5,5'-dicarboxylic acid, 2-amino-5-nitrophenol and polyphosphoric acid were mixed in a mass ratio of 1:1.2:18, stirred at 55°C and 100 rpm for 7 h in a nitrogen atmosphere, cooled to 35°C, poured into deionized water, stirred at 900 rpm until the mass of the precipitate remained unchanged, filtered, washed with 0.4 mol / L sodium hydroxide solution and deionized water for 3 times respectively, and dried at 100°C for 8 h to obtain a benzoxazole intermediate; the benzoxazole intermediate, palladium carbon and N-methylpyrrolidone were mixed in a mass ratio of 1:0.06:9, stirred at 20°C and 100 rpm for 25 h in a hydrogen atmosphere, filtered, poured into deionized water, stirred until the mass of the precipitate remained unchanged, filtered, and dried at 55°C for 10 h to obtain a benzoxazole diamine monomer; (3) Adipic acid and anhydrous ethanol were mixed in a mass ratio of 1:14, stirred at 55°C and 100 rpm for 35 min, 1,5-diaminopentane (0.6 times the mass of adipic acid) was added at a uniform rate within 55 min, the temperature was raised to 70°C and refluxed for 4 h, naturally cooled to room temperature and filtered, washed with anhydrous ethanol three times, and dried at 65°C for 13 h to obtain 1,5-diaminopentane adipate; Adipic acid and anhydrous ethanol were mixed in a mass ratio of 1:14, stirred at 55°C and 100 rpm for 35 min, adipic acid was added at a uniform rate within 55 min The benzoxazole diamine monomer with twice the mass was heated to 70°C and refluxed for 4 hours, naturally cooled to room temperature and then filtered, washed with anhydrous ethanol for 3 times, and dried at 65°C for 13 hours to obtain benzoxazole diamine adipate; 1,5-diaminopentane adipate, benzoxazole diamine adipate and deionized water were mixed at a mass ratio of 1:0.7:15, stirred for 65 minutes at 215°C, 1MPa and 300rpm in a nitrogen atmosphere, heated to 265°C and vacuum polymerized for 1.5 hours, and then allowed to stand for 10 minutes and then supercooled and discharged to obtain modified polyamide; (4) The modified polyamide, modified multi-walled carbon nanotubes, pyrrole, ferric chloride and cupric chloride were mixed in a mass ratio of 1:0.04:0.02:0.01:0.01, and the mixture was extruded and spun using a twin-screw extruder. The mixture was allowed to stand at 95°C for 8 hours and naturally cooled to room temperature to obtain antistatic modified nylon filament.

[0024] Example 2 A method for preparing antistatic modified nylon filaments, the method comprising the following preparation steps: (1) Diethyl (formylmethyl) phosphate, 1-aminopyrrole, anhydrous magnesium sulfate, glacial acetic acid and anhydrous ethanol were mixed in a mass ratio of 1:0.5:0.7:0.35:18, refluxed at 70°C for 6 h in a nitrogen atmosphere, naturally cooled to room temperature and filtered, washed with deionized water and anhydrous methanol for 4 times, dried at 80°C for 12 h, and obtained diethyl pyrrole phosphate; hydroxylated multi-walled carbon nanotubes, diethyl pyrrole phosphate, tetrabutyl titanate and toluene were mixed in a mass ratio of 1:2:0.015:6, stirred at 160°C and 250 rpm for 5 h in a nitrogen atmosphere, naturally cooled to room temperature and filtered, washed with deionized water and anhydrous ethanol for 4 times, dried at 65°C for 24 h, and ground and sieved to obtain modified multi-walled carbon nanotubes; (2) 2,2'-bipyridine-5,5'-dicarboxylic acid, 2-amino-5-nitrophenol and polyphosphoric acid were mixed in a mass ratio of 1:1.3:18.5, stirred at 60°C and 150 rpm for 6 h in a nitrogen atmosphere, cooled to 40°C, poured into deionized water, stirred at 1000 rpm until the mass of the precipitate remained unchanged, filtered, washed with 0.5 mol / L sodium hydroxide solution and deionized water for 4 times respectively, and dried at 105°C for 7 h to obtain a benzoxazole intermediate; the benzoxazole intermediate, palladium carbon and N-methylpyrrolidone were mixed in a mass ratio of 1:0.07:10, stirred at 25°C and 150 rpm for 24 h in a hydrogen atmosphere, filtered, poured into deionized water, stirred until the mass of the precipitate remained unchanged, filtered, and dried at 60°C for 9 h to obtain a benzoxazole diamine monomer; (3) Adipic acid and anhydrous ethanol were mixed at a mass ratio of 1:15, stirred at 60°C and 150 rpm for 30 min, 1,5-diaminopentane (0.7 times the mass of adipic acid) was added at a uniform rate within 60 min, the temperature was raised to 75°C and refluxed for 3 h, naturally cooled to room temperature and filtered, washed with anhydrous ethanol 4 times, and dried at 70°C for 12 h to obtain 1,5-diaminopentane adipate; Adipic acid and anhydrous ethanol were mixed at a mass ratio of 1:15, stirred at 60°C and 150 rpm for 30 min, adipic acid was added at a uniform rate within 60 min 2.5 times the mass of benzoxazole diamine monomer, heated to 75°C and refluxed for 3h, naturally cooled to room temperature and filtered, washed with anhydrous ethanol 4 times, dried at 70°C for 12h, to obtain benzoxazole diamine adipate; 1,5-diaminopentane adipate, benzoxazole diamine adipate and deionized water were mixed at a mass ratio of 1:0.8:20, stirred at 220°C, 2MPa, 350rpm for 60min in a nitrogen atmosphere, heated to 270°C for vacuum polymerization for 1h, left to stand for 15min, discharged from the supercooled water and sliced ​​to obtain modified polyamide; (4) The modified polyamide, modified multi-walled carbon nanotubes, pyrrole, ferric chloride and cupric chloride were mixed in a mass ratio of 1:0.05:0.025:0.015:0.02, extruded and spun using a twin-screw extruder, allowed to stand at 100°C for 7 hours, and naturally cooled to room temperature to obtain antistatic modified nylon filaments.

[0025] Example 3 A method for preparing antistatic modified nylon filaments, the method comprising the following preparation steps: (1) Diethyl (formylmethyl) phosphate, 1-aminopyrrole, anhydrous magnesium sulfate, glacial acetic acid and anhydrous ethanol were mixed in a mass ratio of 1:0.6:0.8:0.4:19, refluxed at 75°C for 5 h in a nitrogen atmosphere, naturally cooled to room temperature and filtered, washed with deionized water and anhydrous methanol for 5 times, dried at 85°C for 11 h, and obtained diethyl pyrrole phosphate; hydroxylated multi-walled carbon nanotubes, diethyl pyrrole phosphate, tetrabutyl titanate and toluene were mixed in a mass ratio of 1:3:0.02:7, stirred at 165°C and 300 rpm for 4 h in a nitrogen atmosphere, naturally cooled to room temperature and filtered, washed with deionized water and anhydrous ethanol for 5 times, dried at 70°C for 23 h, ground and sieved to obtain modified multi-walled carbon nanotubes; (2) 2,2'-bipyridine-5,5'-dicarboxylic acid, 2-amino-5-nitrophenol and polyphosphoric acid were mixed in a mass ratio of 1:1.4:19, stirred at 65°C and 200 rpm for 5 h in a nitrogen atmosphere, cooled to 45°C, poured into deionized water, stirred at 1100 rpm until the mass of the precipitate remained unchanged, filtered, washed with 0.6 mol / L sodium hydroxide solution and deionized water for 5 times respectively, and dried at 110°C for 6 h to obtain a benzoxazole intermediate; the benzoxazole intermediate, palladium carbon and N-methylpyrrolidone were mixed in a mass ratio of 1:0.08:11, stirred at 30°C and 200 rpm for 23 h in a hydrogen atmosphere, filtered, poured into deionized water, stirred until the mass of the precipitate remained unchanged, filtered, and dried at 65°C for 8 h to obtain a benzoxazole diamine monomer; (3) Adipic acid and anhydrous ethanol were mixed in a mass ratio of 1:16, stirred at 65°C and 200 rpm for 25 min, 1,5-diaminopentane (0.8 times the mass of adipic acid) was added at a uniform rate within 65 min, the temperature was raised to 80°C and refluxed for 2 h, naturally cooled to room temperature and filtered, washed with anhydrous ethanol 5 times, and dried at 75°C for 11 h to obtain 1,5-diaminopentane adipate; Adipic acid and anhydrous ethanol were mixed in a mass ratio of 1:16, stirred at 65°C and 200 rpm for 25 min, adipic acid was added at a uniform rate within 65 min The benzoxazole diamine monomer with a mass of 3 times was heated to 80°C and refluxed for 2h, naturally cooled to room temperature and then filtered, washed with anhydrous ethanol 5 times, and dried at 75°C for 11h to obtain benzoxazole diamine adipate; 1,5-diaminopentane adipate, benzoxazole diamine adipate and deionized water were mixed at a mass ratio of 1:0.9:25, stirred at 225°C, 3MPa, and 400rpm in a nitrogen atmosphere for 55min, heated to 276°C and vacuum polymerized for 0.5h, allowed to stand for 20min, discharged from the supercooled water and sliced ​​to obtain modified polyamide; (4) The modified polyamide, modified multi-walled carbon nanotubes, pyrrole, ferric chloride and cupric chloride were mixed in a mass ratio of 1:0.06:0.03:0.02:0.03, and the mixture was extruded and spun using a twin-screw extruder. The mixture was allowed to stand at 105°C for 6 hours and naturally cooled to room temperature to obtain antistatic modified nylon filament.

[0026] Comparative Example 1: A method for preparing antistatic modified nylon filaments, the method comprising the following preparation steps: (1) Hydroxylated multi-walled carbon nanotubes, diethyl (formylmethyl) phosphate, tetrabutyl titanate and toluene were mixed in a mass ratio of 1:2:0.015:6, stirred at 160°C and 250 rpm for 5 h in a nitrogen atmosphere, naturally cooled to room temperature and filtered, washed with deionized water and anhydrous ethanol for 4 times respectively, dried at 65°C for 24 h, ground and sieved through 60 mesh to obtain modified multi-walled carbon nanotubes; (2) 2,2'-bipyridine-5,5'-dicarboxylic acid, 2-amino-5-nitrophenol and polyphosphoric acid were mixed in a mass ratio of 1:1.3:18.5, stirred at 60°C and 150 rpm for 6 h in a nitrogen atmosphere, cooled to 40°C, poured into deionized water, stirred at 1000 rpm until the mass of the precipitate remained unchanged, filtered, washed with 0.5 mol / L sodium hydroxide solution and deionized water for 4 times respectively, and dried at 105°C for 7 h to obtain a benzoxazole intermediate; the benzoxazole intermediate, palladium carbon and N-methylpyrrolidone were mixed in a mass ratio of 1:0.07:10, stirred at 25°C and 150 rpm for 24 h in a hydrogen atmosphere, filtered, poured into deionized water, stirred until the mass of the precipitate remained unchanged, filtered, and dried at 60°C for 9 h to obtain a benzoxazole diamine monomer; (3) Adipic acid and anhydrous ethanol were mixed at a mass ratio of 1:15, stirred at 60°C and 150 rpm for 30 min, 1,5-diaminopentane (0.7 times the mass of adipic acid) was added at a uniform rate within 60 min, the temperature was raised to 75°C and refluxed for 3 h, naturally cooled to room temperature and filtered, washed with anhydrous ethanol 4 times, and dried at 70°C for 12 h to obtain 1,5-diaminopentane adipate; Adipic acid and anhydrous ethanol were mixed at a mass ratio of 1:15, stirred at 60°C and 150 rpm for 30 min, adipic acid was added at a uniform rate within 60 min 2.5 times the mass of benzoxazole diamine monomer, heated to 75°C and refluxed for 3h, naturally cooled to room temperature and filtered, washed with anhydrous ethanol 4 times, dried at 70°C for 12h, to obtain benzoxazole diamine adipate; 1,5-diaminopentane adipate, benzoxazole diamine adipate and deionized water were mixed at a mass ratio of 1:0.8:20, stirred at 220°C, 2MPa, 350rpm for 60min in a nitrogen atmosphere, heated to 270°C for vacuum polymerization for 1h, left to stand for 15min, discharged from the supercooled water and sliced ​​to obtain modified polyamide; (4) The modified polyamide, modified multi-walled carbon nanotubes and cupric chloride were mixed in a mass ratio of 1:0.05:0.02, extruded and spun using a twin-screw extruder, allowed to stand at 100°C for 7 hours, and naturally cooled to room temperature to obtain antistatic modified nylon filaments.

[0027] Comparative Example 2: A method for preparing antistatic modified nylon filaments, the method comprising the following preparation steps: (1) 2,2'-bipyridine-5,5'-dicarboxylic acid, 2-amino-5-nitrophenol and polyphosphoric acid were mixed in a mass ratio of 1:1.3:18.5, stirred at 60°C and 150 rpm for 6 h in a nitrogen atmosphere, cooled to 40°C, poured into deionized water, stirred at 1000 rpm until the mass of the precipitate remained unchanged, filtered, washed with 0.5 mol / L sodium hydroxide solution and deionized water for 4 times respectively, and dried at 105°C for 7 h to obtain a benzoxazole intermediate; the benzoxazole intermediate, palladium carbon and N-methylpyrrolidone were mixed in a mass ratio of 1:0.07:10, stirred at 25°C and 150 rpm for 24 h in a hydrogen atmosphere, filtered, poured into deionized water, stirred until the mass of the precipitate remained unchanged, filtered, and dried at 60°C for 9 h to obtain a benzoxazole diamine monomer; (2) Adipic acid and anhydrous ethanol were mixed at a mass ratio of 1:15, stirred at 60°C and 150 rpm for 30 min, 1,5-diaminopentane (0.7 times the mass of adipic acid) was added at a uniform rate within 60 min, the temperature was raised to 75°C and refluxed for 3 h, naturally cooled to room temperature and filtered, washed with anhydrous ethanol 4 times, and dried at 70°C for 12 h to obtain 1,5-diaminopentane adipate; Adipic acid and anhydrous ethanol were mixed at a mass ratio of 1:15, stirred at 60°C and 150 rpm for 30 min, adipic acid was added at a uniform rate within 60 min 2.5 times the mass of benzoxazole diamine monomer, heated to 75°C and refluxed for 3h, naturally cooled to room temperature and filtered, washed with anhydrous ethanol 4 times, dried at 70°C for 12h, to obtain benzoxazole diamine adipate; 1,5-diaminopentane adipate, benzoxazole diamine adipate and deionized water were mixed at a mass ratio of 1:0.8:20, stirred at 220°C, 2MPa, 350rpm for 60min in a nitrogen atmosphere, heated to 270°C for vacuum polymerization for 1h, left to stand for 15min, discharged from the supercooled water and sliced ​​to obtain modified polyamide; (3) The modified polyamide, hydroxylated multi-walled carbon nanotubes and cupric chloride were mixed in a mass ratio of 1:0.05:0.02, extruded and spun using a twin-screw extruder, allowed to stand at 100°C for 7 hours, and naturally cooled to room temperature to obtain antistatic modified nylon filaments.

[0028] Comparative Example 3: A method for preparing antistatic modified nylon filaments, the method comprising the following preparation steps: (1) Diethyl (formylmethyl) phosphate, 1-aminopyrrole, anhydrous magnesium sulfate, glacial acetic acid and anhydrous ethanol were mixed in a mass ratio of 1:0.5:0.7:0.35:18, refluxed at 70°C for 6 h in a nitrogen atmosphere, naturally cooled to room temperature and filtered, washed with deionized water and anhydrous methanol for 4 times, dried at 80°C for 12 h, and obtained diethyl pyrrole phosphate; hydroxylated multi-walled carbon nanotubes, diethyl pyrrole phosphate, tetrabutyl titanate and toluene were mixed in a mass ratio of 1:2:0.015:6, stirred at 160°C and 250 rpm for 5 h in a nitrogen atmosphere, naturally cooled to room temperature and filtered, washed with deionized water and anhydrous ethanol for 4 times, dried at 65°C for 24 h, and ground and sieved to obtain modified multi-walled carbon nanotubes; (2) Adipic acid and anhydrous ethanol were mixed in a mass ratio of 1:15, stirred at 60°C and 150 rpm for 30 min, 1,5-diaminopentane (0.7 times the mass of adipic acid) was added at a uniform rate within 60 min, the temperature was raised to 75°C and refluxed for 3 h, naturally cooled to room temperature and filtered, washed with anhydrous ethanol 4 times, and dried at 70°C for 12 h to obtain 1,5-diaminopentane adipate; 1,5-diaminopentane adipate and deionized water were mixed in a mass ratio of 1:20, stirred at 220°C, 2 MPa, and 350 rpm in a nitrogen atmosphere for 60 min, heated to 270°C for vacuum polymerization for 1 h, allowed to stand for 15 min, discharged from the supercooled water and sliced ​​to obtain polyamide; (3) Polyamide, modified multi-walled carbon nanotubes, pyrrole, ferric chloride and cupric chloride were mixed in a mass ratio of 1:0.05:0.025:0.015:0.02, extruded and spun using a twin-screw extruder, allowed to stand at 100°C for 7 hours, and naturally cooled to room temperature to obtain antistatic modified nylon filaments.

[0029] Test Case 1. Flame retardancy Test method: The antistatic modified nylon filaments obtained in each example and the comparative example were tested for limiting oxygen index according to GB / T2406.

[0030] 2. Antistatic properties Test method: The antistatic modified nylon filaments obtained in each embodiment and the comparative example are woven into a fabric of 4.5 cm × 4.5 cm in size. According to GB / T12703, the static voltage is measured using a YG(B)342E fabric induction static tester at 25°C and a relative humidity of 65%.

[0031] 3. Mechanical properties Test method: The antistatic modified nylon filaments obtained in each embodiment and the comparative example were tested for breaking strength P0 under the conditions of stretching distance 500 mm, stretching speed 500 mm / min, and pre-tension 39 cN according to GB / T14344.

[0032] 4. Anti-aging Test method: The antistatic modified nylon filaments obtained in each embodiment and the comparative example were aged for 40 hours in a sun aging test box under the conditions of a 300W ultraviolet lamp, a vertical distance of 20cm, 25°C, and a relative humidity of 65%. Then, according to GB / T14344, under the conditions of a stretching gauge of 500mm, a stretching speed of 500mm / min, and a pre-tension of 39cN, the breaking strength P1 was tested, and the aging rate was calculated as (P0-P1) / P0*100%.

[0033] Table 1 below shows the analysis results of the antistatic, flame retardant, anti-aging and mechanical properties of the antistatic modified nylon filaments of Examples 1 to 3 of the present invention and Comparative Examples 1 to 3.

[0034]

[0035] From the comparison of the experimental data of Examples 1 to 3 and Comparative Examples 1 to 3 in Table 1, it can be found that the antistatic modified nylon filaments prepared by the present invention have good antistatic, flame retardant, anti-aging and mechanical properties.

[0036] By comparison, compared with Example 1, Examples 1, 2, and 3, the electrostatic voltage is lower and the breaking strength is higher, which indicates that the pyrrole on the surface of the modified multi-walled carbon nanotubes can form long chains of polypyrrole, and the polypyrrole molecular structure contains a conjugated structure that can provide free electrons, providing a charge conduction channel, and further improving the antistatic properties of the antistatic modified nylon filaments; at the same time, the nitrogen atoms in the polypyrrole can coordinate with metal ions to form metal-nitrogen coordination bonds, forming a cross-linked network, and improving the mechanical properties of the antistatic modified nylon filaments.

[0037] By comparison, Examples 1, 2, and 3 have lower electrostatic voltage, higher breaking strength and limiting oxygen index than Comparative Example 2, which indicates that the grafting of phosphorus elements can form a protective layer during the combustion process, capture free radicals in the combustion flame, cut off the flame oxidation chain reaction, and improve the flame retardant properties of the antistatic modified nylon filament.

[0038] By comparison, compared with Example 3, Examples 1, 2, and 3 have lower electrostatic voltage and aging rate and higher breaking strength, which illustrates that benzoxazole intermediates are generated by cyclodehydrogenation under the action of polyphosphoric acid, and benzoxazole diamine monomers are obtained by reducing nitro groups. The molecular structure of benzoxazole diamine monomers has a large number of conjugated transition π electron systems, which have strong absorption of ultraviolet light (300-400nm) waves that are invisible in sunlight, and convert them into visible light wavelengths of 420-440nm and reflect them, thereby improving the anti-aging properties of the antistatic modified nylon filaments. At the same time, the bipyridine structure contained in the benzoxazole diamine monomer can coordinate with metal ions to form a stable metal-ligand cross-linked network between the polyamide main chain and the modified multi-walled carbon nanotubes. The electron cloud distribution of bipyridine itself can also affect the electron density of the metal center, promote electron migration, and improve the mechanical properties and antistatic properties of the antistatic modified nylon filaments.

[0039] The specific implementation methods described above further illustrate the objectives, technical solutions and beneficial effects of the present invention in detail. It should be understood that the above description is only a specific implementation method of the present invention and is not intended to limit the scope of protection of the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the scope of protection of the present invention.

Claims

1. A method for preparing antistatic modified nylon filament, characterized in that: The antistatic modified nylon filament is prepared by melt spinning after uniformly mixing modified polyamide, modified multi-walled carbon nanotubes, pyrrole, ferric chloride and cupric chloride; the modified polyamide is prepared by reacting 2,2'-bipyridine-5,5'-dicarboxylic acid with 2-amino-5-nitrophenol, and then reacting with adipic acid and 1,5-diaminopentane; the modified multi-walled carbon nanotube is prepared by reacting diethyl (formylmethyl) phosphate with 1-aminopyrrole, and then reacting with hydroxylated multi-walled carbon nanotube.

2. The method for preparing antistatic modified nylon filament according to claim 1, characterized in that: The method comprises the following preparation steps: (1) Mix diethyl (formylmethyl) phosphate, 1-aminopyrrole, anhydrous magnesium sulfate, glacial acetic acid and anhydrous ethanol in a mass ratio of 1: (0.4-0.6): (0.6-0.8): (0.3-0.4): (17-19), reflux at 65-75°C in a nitrogen atmosphere for 5-7 hours, cool naturally to room temperature and filter, wash with deionized water and anhydrous methanol for 3-5 times respectively, and dry at 75-85°C for 11-13 hours to obtain diethyl pyrrole phosphate. ; Mix hydroxylated multi-walled carbon nanotubes, diethyl pyrrole phosphate, tetrabutyl titanate and toluene in a mass ratio of 1: (1-3): (0.01-0.02): (5-7), stir at 155-165°C and 200-300rpm for 4-6 hours in a nitrogen atmosphere, cool naturally to room temperature and filter, wash with deionized water and anhydrous ethanol for 3-5 times respectively, dry at 60-70°C for 23-25 ​​hours, grind and sieve 55-65 mesh to obtain modified multi-walled carbon nanotubes; (2) Mix 2,2'-bipyridine-5,5'-dicarboxylic acid, 2-amino-5-nitrophenol and polyphosphoric acid in a mass ratio of 1:(1.2-1.4):(18-19), stir at 55-65°C and 100-200 rpm for 5-7 h in a nitrogen atmosphere, cool to 35-45°C, pour into deionized water, stir at 900-1100 rpm until the precipitate mass remains unchanged, filter, and dilute with 0.4-0.6 mol / L sodium hydroxide solution and deionized water, respectively. Wash 3 to 5 times, dry at 100 to 110°C for 6 to 8 hours to obtain a benzoxazole intermediate; mix the benzoxazole intermediate, palladium carbon and N-methylpyrrolidone in a mass ratio of 1: (0.06 to 0.08): (9 to 11), stir in a hydrogen atmosphere at 20 to 30°C and 100 to 200 rpm for 23 to 25 hours, filter, pour into deionized water, stir until the precipitate remains unchanged in mass, filter, and dry at 55 to 65°C for 8 to 10 hours to obtain a benzoxazole diamine monomer; (3) 1,5-diaminopentane adipate, benzoxazole diamino adipate and deionized water are mixed in a mass ratio of 1: (0.7-0.9): (15-25), stirred for 55-65 min at 215-225° C., 1-3 MPa and 300-400 rpm in a nitrogen atmosphere, heated to 265-276° C. for vacuum polymerization for 0.5-1.5 h, allowed to stand for 10-20 min, discharged from the supercooled water and sliced ​​to obtain a modified polyamide; (4) The modified polyamide, modified multi-walled carbon nanotubes, pyrrole, ferric chloride and cupric chloride are mixed in a mass ratio of 1: (0.04-0.06): (0.02-0.03): (0.01-0.02): (0.01-0.03), and the mixture is extruded and spun using a twin-screw extruder. The mixture is allowed to stand at 95-105°C for 6-8 hours and naturally cooled to room temperature to obtain antistatic modified nylon filament.

3. The method for preparing antistatic modified nylon filament according to claim 2, characterized in that: The reaction equation of diethyl pyrrole phosphate in step (1) is: .

4. The method for preparing antistatic modified nylon filament according to claim 2, characterized in that: The reaction equation for modifying multi-walled carbon nanotubes in step (1) is: .

5. The method for preparing antistatic modified nylon filament according to claim 2, characterized in that: The reaction equation of the benzoxazole diamine monomer in step (2) is: .

6. The method for preparing antistatic modified nylon filament according to claim 2, characterized in that: The 1,5-diaminopentane adipate in step (3) is prepared by mixing adipic acid and anhydrous ethanol in a mass ratio of 1:(14-16), stirring at 55-65° C. and 100-200 rpm for 25-35 min, adding 1,5-diaminopentane in an amount of 0.6-0.8 times the mass of adipic acid at a uniform rate within 55-65 min, heating to 70-80° C. and reflux for 2-4 h, naturally cooling to room temperature and filtering, washing with anhydrous ethanol for 3-5 times, and drying at 65-75° C. for 11-13 h.

7. The method for preparing antistatic modified nylon filament according to claim 2, characterized in that: The benzoxazole diamino adipate in step (3) is prepared by mixing adipic acid and anhydrous ethanol in a mass ratio of 1:(14-16), stirring at 55-65° C. and 100-200 rpm for 25-35 min, adding benzoxazole diamino monomer 2-3 times the mass of adipic acid at a uniform rate within 55-65 min, heating to 70-80° C. and reflux for 2-4 h, naturally cooling to room temperature and filtering, washing with anhydrous ethanol for 3-5 times, and drying at 65-75° C. for 11-13 h.

8. The method for preparing antistatic modified nylon filament according to claim 2, characterized in that: The reaction equation of the modified polyamide in step (3) is: ; R1 is ; R2 is .

9. The method for preparing antistatic modified nylon filament according to claim 2, characterized in that: The reaction equation of the antistatic modified nylon filament in step (4) is: ; R1 is R2 is .

10. The method for preparing antistatic modified nylon filament according to claim 2, characterized in that: The main process parameters of the spinning process in step (4) are: zone 1 245°C, zone 2 250°C, zone 3 250°C, zone 4 255°C, zone 5 255°C, side blowing temperature of 16.5°C, wind speed of 0.4m / s, stretching temperature of 140-150°C, and stretching multiple of 1.2.

Citation Information

Cited By

  • Antibacterial easy-to-clean fabric and preparation method thereof

    CN120099788A

  • Antibacterial and easy-to-clean fabric and preparation method thereof

    CN120099788B

  • Preparation method of water-based primer for lithium battery foil

    CN120137469A

  • Antistatic modified polyamide fiber and preparation method thereof

    CN120174504A